2016
DOI: 10.1080/14756366.2016.1177523
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of anti-carbonic anhydrase IX antibody in hydrogel microspheres for tumor targeting

Abstract: Encapsulation is a well-established method of biomaterial protection, controlled release, and efficient delivery. Here we evaluated encapsulation of monoclonal antibody M75 directed to tumor biomarker carbonic anhydrase IX (CA IX) into alginate microbeads (SA-beads) or microcapsules made of sodium alginate, cellulose sulfate, and poly(methylene-co-guanidine) (PMCG). M75 antibody release was quantified using ELISA and its binding properties were assessed by immunodetection methods. SA-beads showed rapid M75 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Lin et al ( 2017 ) also surface functionalized triptolide-loaded liposomes with anti-CA IX antibody to target CA IX-positive human non-small cell lung cancer cells (A549) and A549 tumor spheroids, resulting in the efficient cell apoptosis as compared to free drug and non-targeted liposomes. In a study by Takacova et al ( 2016 ), instead of surface functionalization, the scientists encapsulated the monoclonal antibody M75 into alginate microbeads and sodium alginate-cellulose sulfate-poly(methylene-co-guanidine) based microcapsules to knock down the CA IX expressed by tumor cells.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…Lin et al ( 2017 ) also surface functionalized triptolide-loaded liposomes with anti-CA IX antibody to target CA IX-positive human non-small cell lung cancer cells (A549) and A549 tumor spheroids, resulting in the efficient cell apoptosis as compared to free drug and non-targeted liposomes. In a study by Takacova et al ( 2016 ), instead of surface functionalization, the scientists encapsulated the monoclonal antibody M75 into alginate microbeads and sodium alginate-cellulose sulfate-poly(methylene-co-guanidine) based microcapsules to knock down the CA IX expressed by tumor cells.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…Indeed, G250, formulated as chimeric IgG1 monoclonal antibody and denominated girentuximab, was the first CA IX inhibitor to enter clinical trials [ 57 ], being actually in Phase III, although it seems that its development has been interrupted due to lack of efficacy [ 58 ]. Thus, no other details will be discussed about this Mab, but Pastorekova’s group [ 59 , 60 ] proposed several interesting approaches based both on antibodies that inhibit the catalytic activity as well as those that target the PG domain of CA IX (and do not inhibit the CO 2 hydrase activity of the enzyme). For example the mouse monoclonal antibody VII/20 was shown to bind to the catalytic domain of CA IX, leading to an efficient receptor-mediated internalization of the antibody-enzyme conjugate, which is the main process that regulates abundance and signaling of cell surface proteins [ 60 ].…”
Section: Antibodies Targeting Ca IX and Xii As Antitumor Agentsmentioning
confidence: 99%
“…This internalization has a considerable impact on immunotherapy and in this particular case elicited significant anticancer effects in a mouse xenograft model of colorectal cancer [ 60 ]. The same group [ 59 ] demonstrated that the monoclonal antibody M75 (targeting the PG domain of CA IX and widely used as a reagent in immune-histochemical studies [ 10 , 17 ]) can be encapsulated into alginate microbeads or microcapsules made of sodium alginate, cellulose sulfate, and poly(methylene-co-guanidine), which afforded a rapid M75 antibody release at pH 6.8 (characteristic of the acidic tumors) compared to pH 7.4 (the physiologic, normal pH) [ 59 ].…”
Section: Antibodies Targeting Ca IX and Xii As Antitumor Agentsmentioning
confidence: 99%
“…by endocytosis (Javier et al 2008). Targets of PEMC are numerous and include different cancer cells and thrombocytes (Javier et al 2008;Takacova et al 2016). The delivery of PEMC to the target organs or tissue may be achieved by various means including peritoneal injections (De Koker et al 2009;Federici et al 2015).…”
Section: Notably In the Presence Of Lps Neutrophil Activation Bymentioning
confidence: 99%